Spiritual Service, Sacred Toponymics and Heroic Ancestor as Forms of the Description of Russian Islam before the Nation-building Period - D. R. Gilmutdinov (Концепт: философия, религия, культура, 2025)
The article focuses on the creation of the image of the Muslim community of inner Russia in the historical writings of the pre-revolutionary Tatar-Bashkir elite. The relevance of the study stems from the need to clarify the origin of their present-day national and religious identity. The study materials include established biographical collections, focusing primarily on the biographies of imams and the history of mosques. The authors of the discussed printed works (Sh. Marjani, R. Fahretdin and Muhammad Murad-Ramzi) represent a modernizing society of the middle of the 19th – early 20th centuries, when the framework of the community was made of official institutions. The aim of the research is to trace key ideas representing the worldview as reflected in the studied collections. To this end, the study addresses the following objectives:1) to trace the process of forming the internal image of Russian Muslims; 2) to analyze the interpretation of the conception of ideal spaces through the prism of social constructivism and religious anthropology; 3) to identify specific characteristics of self-representation, writing style and cultural background of the collections. Apart from the historic-genetic, axiological and hermeneutic methods, an anthropological approach to social constructivism theories and ideas of imaginary communities were applied. As a result, it was shown that the collection tends to be centered around the personality of the compiler and his religious and ideological perspective. It is noted that religious ideas and social practices of the community strongly correlate with the development of the unique identity of the Tatar-Muslim community. An incomplete listing of the collection only favors the compilers’ inclination to express their personal likes and dislikes. Unlike modern encyclopedias, the studied collections are somewhat sketchy and do not represent a comprehensive worldview. However, they serve the universal idea of the search for unity by intellectuals and religious leaders of the time. The research fills an important gap in the transformation of the Muslim diaspora in Russia into a secular nation. As a result, the basic principles of the feeling of the collective in the pre-national period were identified. The author concludes that 1) the internal image of Tatar Muslims in Russia was formed both historically and under the influence of Tatar Muslim intellectual elites; 2) social constructivism methodology made it possible to trace the shift from Bulgar as a sacred center to authoritative genealogies of imams which complete the self-representation image of the community; 3) by the beginning of the 20th century, the community center moved from Kazan to the border of Tatars and Bashkirs tribes, the Muftiate in Ufa became a platform for the consolidation of the Turkic-Muslim nationalities of Russia and representation of their religious authority and formal status.